Desenvolvimento de um potenciostato/galvanostato portátil e eletrodos impressos para determinações in situ em análises em fluxo com transmissão de dados em tempo real - Santos, Vagner Bezerra dos (Universidade Federal de São Carlos, 2013)
The main purpose of this work was to develop a potentiostat/galvanostat (PG004) to perform the electroactive metallic ions determination in water samples automatically. A dry thermostated electrochemical cell and a flow system with multicommutation were developed based on the use of the solenoid micropumps and valves with screen-printed electrodes (SPE) for the electrochemical measurements with detection employing stopped flow or continuous flow techniques. Two types of the SPE were developed: i) the SPE based on bismuth film (SPE-BiF) electrochemically deposited for on-line and in situ or ex situ modes, and ii) the boron doped diamond coupled to the SPE (SPE-BDD). These devices, and the electrodes were optimized and their performances were evaluated firstly by employing commercially available potentiostat/galvanostat. Thus, individual or simultaneous determination of Zn2+, Cd2+, and Pb2+ ions were carried out using the stopped flow technique and detection employing square-wave anodic stripping voltammetry (SWASV) to the SPE-BiF, and differential pulse (DPASV) for the SPE-BDD. Limits of detection (LDs) of 1.60 μg L-1, 0.30 μg L-1 and 0.09 μg mL-1, respectively were obtained for the simultaneous determination of Zn2+, Cd2+, and Pb2+ ions by using the SPE BiF ex-situ with SWASV. For the BDD-SPE-DPASV, LDs of 2.50 μg L-1, 0.38 μg L-1 and 0.10 μg L-1 were obtained, respectively, for the determination mentioned previously. Determination of analytes individually or simultaneously were also carried out with SPE-BDD employing multiple pulse amperometry (MPA), and LDs of 150 μg L-1, 87.0 μg L-1 and 13.0 μg mL-1 were obtained respectively for simultaneous determination of Zn2+, Cd2+, and Pb2+ ions with a sampling rate of 54 determinations per hour. In parallel with the electroanalyticals determinations, the PG004 was developed according to the following sequence. i) development of the electronic circuits; ii) calibrations of the PG004; iii) assembly of the PG004 with the flow module coupled to it; iv) coupling of the peripheral devices to the CPU of the PG004 for the wireless transmission of the data with Bluetooth®, Wi-Fi® and 3G protocol, and a GPS receiver), and v) connections of the power unit (12 V batteries) and solar board. Then, the PG004 was employed to determine Cd2+ and Pb2+ ions with SPE-BDD and SWASV in laboratory to simulate in situ conditions. Then, the PG004 was placed to the field for in situ determinations of Cd2+ and Pb2+ ions with good results: i) individual and simultaneous determinations of the Cd2+ and Pb2+ ions with recoveries ranged from 93.3 to 109%; ii) voltammograms with no noises and with good resolutions; iii) reception of the geographical coordinates using the GPS receiver and sending experimental data via mobile technology (GPRS); iv) great autonomy of energy due to the solar board; v) automated capture, filtration and thermostatic temperature control for in situ analysis; vi) SPE-BDD and SPE-BiF reusable at the end of the analysis and vii) low waste generation per determination (700 μL).
Development of a portable potentiostat/galvanostat and screen-printed electrodes for in situ determinations in flow analysis with data transmission in real time
Keywords: Instrumentação; Potenciostato; Galvanostato; Eletrodos impressos; Análise em fluxo; Determinações in situ.; CIENCIAS EXATAS E DA TERRA::QUIMICA